Canine Prophylactic Gastropexy: A Cross‐Sectional Study of Irish Veterinary Professionals’ Attitudes and Current Practices - Hannah Donnelly; Karen Dunne (Veterinary Medicine and Science)
Abstract Background Prophylactic gastropexy reduces the occurrence of gastric dilatation and volvulus (GDV) in dogs, but ethical concerns exist due to its invasiveness. Research on veterinary professionals’ opinions of the procedure is lacking, with no data having been published either in the Republic of Ireland (ROI) or further afield. This study was designed to bridge this knowledge gap, by identifying current practices in the ROI and examining veterinary professionals’ views of the procedure. Methods A cross‐sectional study was conducted with 43 registered veterinary practitioners (VPs) and 45 registered veterinary nurses (RVNs) in the ROI, on their current practices and views on prophylactic gastropexy. Data was analysed using Microsoft Excel, with descriptive statistical analysis of quantitative data and qualitative data subjected to thematic analysis. Results Two themes relating to prophylactic gastropexy were identified: enabling perceptions and disabling perceptions. Enabling perceptions included reduced risk of GDV, cost‐effectiveness, improved quality of life and reduced anaesthetic risk. Disabling perceptions included anaesthetic and surgical risks, inability to prevent gastric dilation, potential gastropexy breakdown, cost and post‐operative complications. In addition, ethical concerns were raised regarding the procedure's invasiveness, its potential interference with natural selection and the fact that it could encourage the use of surgical solutions to problems created by improper breeding practices. Conclusions Due to ethical issues associated with the procedure, the decision to perform a prophylactic gastropexy relies on multiple patient factors, the procedure's invasiveness, the timing of the procedure and its impact on future health. This study failed to account for the owner's perspective, necessitating further research.